Livelihood and Resistance: Peasants and the Politics of Land in Peru - Moore, Jerry D. (Labour / Le Travail, 1991)
The article reviews the book, "Livelihood and Resistance: Peasants and the Politics of Land in Peru," by Gavin Smith.
Keywords: BOOKS – Reviews; FINE; Sidney; Nonfiction; VIOLENCE in the Model City: The Cavanaugh Administration; Race Relations & the Detroit Riot of 1967 (Book); violence